Pengaruh Pemberian Reward dan Punishment terhadap Kedisiplinan Siswa di SMA - Putra Isra Mahendra; Sulaiman Sulaiman (Pendidikan Agama Islam STIT Palapa Nusantara, 2023)
This research was motivated by the low level of student discipline at school. This study aims to 1) to find out how the level of reward and punishment is given at SMA Negeri 1 Ulakan Tapakis 2) to find out how the level of student discipline at SMA Negeri 1 Ulakan Tapakis 3) to find out how the effect of giving reward and punishment on student discipline at SMA Negeri 1 Ulakan Tapakis. This research uses quantitative correlational research. The population in this study was 587 students at SMA Negeri 1 Ulakan Tapakis. The sample technique for this study was random sampling of 71 students with details of 23 students (class X E6), 24 students (class XI F2) and 24 students (class XII.S2) SMAN 1 Ulakan Tapakis. Data collection is carried out through questionnaires and documentation. Data analysis used descriptive data analysis and hypothesis testing, with reward (X1) and punishment (X2) as independent variables and student discipline (Y) as the dependent variable using SPSS version 26. Based on the research results obtained through a questionnaire 1) The level of reward is on average (Mean) 46.62 as many as 66% of students are in the medium category. 2) The level of punishment is proven by an average of 73.31, as many as 63% of students are in the medium category. 3) There is an influence between reward and punishment on student discipline as evidenced by the R square test of 0.485 (48.5%) which shows that there is an influence between the independent variables and the dependent variable.